2023
DOI: 10.1371/journal.pntd.0011398
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based advice on timing and location of tsetse control measures in Shimba Hills National reserve, Kenya

Abstract: Controlling tsetse flies is critical for effective management of African trypanosomiasis in Sub-Saharan Africa. To enhance timely and targeted deployment of tsetse control strategies a better understanding of their temporal dynamics is paramount. A few empirical studies have explained and predicted tsetse numbers across space and time, but the resulting models may not easily scale to other areas. We used tsetse catches from 160 traps monitored between 2017 and 2019 around Shimba Hills National Reserve in Kenya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…This finding is consistent with prior research that examined temporal patterns of abundance, such as by Gachoki et al (2023a), who found that tsetse numbers rose with increased rainfall but then declined when rainfall increased for more than a month. Intense rainfall can lead to excessive water accumulation, increasing soil moisture, which, in turn, can lead to the submerging or dislodging of buried pupae, ultimately causing a decrease in tsetse populations (Omoogun et al, 1989;Lukaw et al, 2014;Ngonyoka, et al, 2017b;Signaboubo et al, 2021).…”
Section: National Scale Tsetse Mapping With Spatially Limited Datasupporting
confidence: 91%
See 4 more Smart Citations
“…This finding is consistent with prior research that examined temporal patterns of abundance, such as by Gachoki et al (2023a), who found that tsetse numbers rose with increased rainfall but then declined when rainfall increased for more than a month. Intense rainfall can lead to excessive water accumulation, increasing soil moisture, which, in turn, can lead to the submerging or dislodging of buried pupae, ultimately causing a decrease in tsetse populations (Omoogun et al, 1989;Lukaw et al, 2014;Ngonyoka, et al, 2017b;Signaboubo et al, 2021).…”
Section: National Scale Tsetse Mapping With Spatially Limited Datasupporting
confidence: 91%
“…In all regions, the traps were emptied every two days, with two or four repetitions per month (see Table 5.1). Although in previous studies (Gachoki et al, 2021(Gachoki et al, , 2023b(Gachoki et al, , 2023a data from traps at the same, or similar, locations were used, those studies did not use the 2021 data used here. The G. pallidipes tsetse species was the sole species that occurred in all sampling sites and accounted for the majority of trapped tsetse species (Table 1).…”
Section: Tsetse Abundance Datamentioning
confidence: 99%
See 3 more Smart Citations